The Belgrade opus of architect Milutin Jovanović (1930-1941) - Gačić Ivanov, Jelena (Arhitektura i urbanizam, 2023)
Milutin Jovanović belongs to the generation of architects who significantly contributed to the urban and architectural development of Belgrade between the two world wars. However, since there has been no adequate valorization of his creativity, a complete list of his achievements and basic biographical data have remained completely unknown. By reconstructing Jovanović’s works, chronologically systematized data about his movement in the architectural profession was obtained. He began his professional engagement as an assistant at the architectural department of the Belgrade Technical Faculty, and later devoted himself to private practice. During the entire interwar period, Jovanović designed dozens of residential buildings and one hotel, and was also dedicated to other design tasks. He was hired by wealthy representatives of the middle class – merchants, clerks, doctors, entrepreneurs and many others, for whom he designed predominantly representative high-rise residential buildings throughout the central city core. In accordance with the developments on the architectural scene of that time, respecting the requests of the clients, his achievements were in two dominant stylistic directions – academicism and modernism. The discovery of buildings designed in the spirit of modernism is particularly significant, because for a long time it was considered that Jovanović’s main style was academicism. Given the lack of personal legacy and complete historiographical sources, the research was based on studying the fund of the Technical Directorate of the City of Belgrade stored in the Historical Archive of Belgrade. Therefore, this work is the first monographic review of the life and work of the architect Milutin Jovanović.